2021
DOI: 10.3389/fonc.2021.676583
|View full text |Cite
|
Sign up to set email alerts
|

Combined Radiochemotherapy: Metalloproteinases Revisited

Abstract: Besides cytotoxic DNA damage irradiation of tumor cells triggers multiple intra- and intercellular signaling processes, that are part of a multilayered, treatment-induced stress response at the unicellular and tumor pathophysiological level. These processes are intertwined with intrinsic and acquired resistance mechanisms to the toxic effects of ionizing radiation and thereby co-determine the tumor response to radiotherapy. Proteolysis of structural elements and bioactive signaling moieties represents a major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 185 publications
(244 reference statements)
0
6
0
Order By: Relevance
“…Another adipogenic marker, TIMP1 (tissue inhibitor of matrix metalloproteinase 1), was also increased in the circulation of DIO mice. TIMP1 has been reported to promote cell proliferation in TNBC and can modulate the radiosensitivity of cancer cells based on its enzymatic inhibition characteristics [59][60][61]. Whether TIMP1 plays a role in coordination with SERPINE1 in this scenario warrants further investigation.…”
Section: Discussionmentioning
confidence: 98%
“…Another adipogenic marker, TIMP1 (tissue inhibitor of matrix metalloproteinase 1), was also increased in the circulation of DIO mice. TIMP1 has been reported to promote cell proliferation in TNBC and can modulate the radiosensitivity of cancer cells based on its enzymatic inhibition characteristics [59][60][61]. Whether TIMP1 plays a role in coordination with SERPINE1 in this scenario warrants further investigation.…”
Section: Discussionmentioning
confidence: 98%
“…We recently reported that IR-induced endothelial cell migration is strongly mediated by tumor cell-located ADAM17 ( 19 , 21 ). In subcutaneous and orthotopic lung tumor models, ADAM17 inhibition by the novel ADAM17-specific therapeutic antibody MEDI3622 in combination with radiotherapy induced a strong anti-angiogenic effect and tumor shrinkage ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…We here describe a unique interrelation between EphA2 and the disintegrin and metalloproteinase ADAM17 alone and in response to irradiation. ADAM17 is involved in the processing of the extracellular matrix and the release of various growth factors and cytokines that contribute to the remodeling of the TME and facilitate tumor cell dissemination ( 19 ). We recently have shown that IR enhances ADAM17 activity in NSCLC cell lines which contributes not only to the radioprotection of the tumor itself, but also its vasculature ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, these inhibitors also demonstrated an increased affinity toward the related matrix metalloproteinase ADAM10. Only in the last decade, highly specific anti-human ADAM17-directed antibodies were developed binding ADAM17 in subnanomolar ranges ( 23 ). Characteristic for MEDI3622 is its high target sensitivity as it recognizes the surface loop sIVa- sIVb β-hairpin on the M-domain, unique for ADAM17 ( 14 ).…”
Section: Discussionmentioning
confidence: 99%